2003
DOI: 10.1039/b306156f
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, conformational analysis and nucleic acid hybridisation properties of thymidyl pyrrolidine-amide oligonucleotide mimics (POM)Electronic supplementary information (ESI) available: experimental details (16 Figures, 3 Tables). See http://www.rsc.org/suppdata/ob/b3/b306156f/

Abstract: Pyrrolidine-amide oligonucleotide mimics (POM) 1 were designed to be stereochemically and conformationally similar to natural nucleic acids, but with an oppositely charged, cationic backbone. Molecular modelling reveals that the lowest energy conformation of a thymidyl-POM monomer is similar to the conformation adopted by ribonucleosides. An efficient solution phase synthesis of the thymidyl POM oligomers has been developed, using both N-alkylation and acylation coupling strategies. 1H NMR spectroscopy confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Indeed X‐ray crystallographic evidence, along with molecular modelling and NMR spectroscopy data suggest that when protonated, the pyrrolidine ring of POM oligomers can favour an N 1′‐ endo (pseudo‐ C 3′‐ endo ) conformation similar to that adopted by ribose in RNA 21. 22 The C 3′‐ endo conformation is known to favour the formation of RNA A‐type duplexes;29 this can also explain why the rate of annealing of POM to RNA is increased to a greater extent than is the rate of association/dissociation with DNA upon the lowering of pH. Additionally, in the free amine form inversion of configuration of the pyrrolidine nitrogen is possible and the resulting equilibrium between configurations can also lead to a reduction in the rate of association/dissociation at higher pH.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed X‐ray crystallographic evidence, along with molecular modelling and NMR spectroscopy data suggest that when protonated, the pyrrolidine ring of POM oligomers can favour an N 1′‐ endo (pseudo‐ C 3′‐ endo ) conformation similar to that adopted by ribose in RNA 21. 22 The C 3′‐ endo conformation is known to favour the formation of RNA A‐type duplexes;29 this can also explain why the rate of annealing of POM to RNA is increased to a greater extent than is the rate of association/dissociation with DNA upon the lowering of pH. Additionally, in the free amine form inversion of configuration of the pyrrolidine nitrogen is possible and the resulting equilibrium between configurations can also lead to a reduction in the rate of association/dissociation at higher pH.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the previous observations with POM homopolymers, which also hybridise more slowly than do native nucleic acids. [20][21][22][23][24][25] The first mixed-sequence POM oligomer Lys-POM-TCA-CAACTT-NH 2 (1) was synthesised with an N-terminal lysine residue to enable comparison with the isosequential PNA, which requires the Lys residue to improve its solubility. [26] It is possible that attachment of Lys to a POM or PNA oligomer will have an effect on the DNA and RNA hybridisation properties.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
See 1 more Smart Citation
“…One approach is the incorporation of neutral internucleoside linkages that eliminate mutual repulsions between the negatively charged phosphodiester backbones. Another approach is to replace the entire phosphodiester backbone, such as in the cases of peptide nucleic acid (PNA), phosphonic ester nucleic acids (PHONA), and nucleic acid analogue peptide (NAAP) . Recent studies have shown that the introduction of positively charged groups at multiple sites in the backbone, , sugar, or base can produce stable duplexes and triplexes . Our approach is to replace the phosphodiester linkages with positively charged achiral guanidinium groups.…”
Section: Introductionmentioning
confidence: 99%